2021
DOI: 10.3390/pathogens10010030
|View full text |Cite
|
Sign up to set email alerts
|

Felid Cardiopulmonary Nematodes: Dilemmas Solved and New Questions Posed

Abstract: In the past decade cardiopulmonary nematodes affecting felids have become a core research topic in small animal parasitology. In the late 2000s, an increase in studies was followed by unexpected findings in the early 2010s, which have stimulated research teams to start investigating these intriguing parasites. Prolific scientific debate and exchanges have then fostered field and laboratory studies and epizootiological surveys. New data have improved basic and applied knowledge, solved dilemmas and posed new qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 90 publications
(355 reference statements)
0
82
0
Order By: Relevance
“…No L1 of lungworms nematodes were detected in the Iberian lynx and mesocarnivores, even though previous studies have reported Aelurostrongylus abstrusus, Oslerus rostratus, Angiostrongylus chabaudi, and nematodes of the genus Troglostrongylus in wild/domestic cats and other wild Felidae species [30]. A. abstrusus was previously recorded in the Eurasian lynx (Lynx lynx) with a prevalence of 17% [31].…”
Section: Discussionmentioning
confidence: 80%
“…No L1 of lungworms nematodes were detected in the Iberian lynx and mesocarnivores, even though previous studies have reported Aelurostrongylus abstrusus, Oslerus rostratus, Angiostrongylus chabaudi, and nematodes of the genus Troglostrongylus in wild/domestic cats and other wild Felidae species [30]. A. abstrusus was previously recorded in the Eurasian lynx (Lynx lynx) with a prevalence of 17% [31].…”
Section: Discussionmentioning
confidence: 80%
“…The cat lungworm A. abstrusus has been described in many wild felid species, though confirmed cases are few [ 7 , 80 ]. This parasite unequivocally infects European wildcats, as proven by epizootiological surveys and case reports [ 11 , 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This additional examination was based either on the recent evidence of taxonomical, biological, and epizotiological unresolved issues for some cardio-respiratory nematodes, as for Angiostrongylus spp., Aelurostrongylus abstrusus , Troglostrongylus spp. [ 7 , 13 ], or the necessity to corroborate the microscopic data for poorly known nematodes, such as Cylicospirura spp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations